Two asymmetric cylindrical dielectric resonator loaded dual port multiple‐input multiple‐output antenna for wide band application with circular polarization attributes. (23rd March 2022) - Dwivedi, Ajay Kumar; K.N., Nagesh; Kumar, H. Venkatesh; Singh, Suyash Kumar; Mungara, Jitendranath; Sharma, Anand; Singh, Vivek
Summary: A novel multiple‐input multiple‐output double asymmetrical cylindrical dielectric resonator antenna (MIMO‐DCDRA) with modified stub line feed is discussed and proposed in this work. Two unequal CDRA are placed diagonally to each other and are electromagnetically coupled with feeding arrangement via two asymmetrical circular apertures. By performing the optimization of the dimensional parameters, a significant impedance bandwidth of 70.84% ranging from 2.87 to 5.76 GHz and axial ratio bandwidth (ARBW) of 34.89% is obtained. Antenna gain is about 5.0 dBi within the operating frequency. The proposed MIMO‐DCDRA exhibits a low mutual coupling of (| S 21 | & | S 12 | < −20 dB) with the incorporation of a neutralization line. There are various diversity parameters that are also discussed in terms of mutual coupling, envelop correlation coefficient (ECC < 0.002), diversity gain (DG > 9.995), and channel capacity loss (CCL < 0.3 bits/s/Hz) over the entire impedance bandwidth. Abstract : In this communication, two asymmetrical cylindrical dielectric resonators loaded MIMO antenna is designed and analyzed for sub‐6‐GHz frequency range applications. The positional orientation of two DRA with respect to each other is investigated to achieve the circular polarization feature.